Niveles de levadura de cerveza (Saccharomyces cerevisiae) en el crecimiento y engorde de pollos criollo en la finca experimental La María - Vera Ruiz, Franklin Galo (2015)
Poultry flock in the State Technical University of Quevedo YeaSacc using yeast at various levels in promoting growth of native chickens were assessed objectives: To assess the levels of yeast (Saccharomyces cerevisiae) in growing and fattening Creole chickens, establish the best level of yeast (Saccharomyces cerevisiae) and know the profitability of the treatments under study. For the study a total of 160 Creole chicken divided into five treatments and four repetitions using Completely Randomized Design (DCA) were used, variables that were evaluated were feed intake (g), weight gain (g), feed conversion , carcass weight (g) cost / benefit ratio in the stages of inception, growth and fattening. To feed intake higher values were reported in the initial phase (583.64 g) and fattening (3569.04 g) in the control treatment and the growth phase treatment with 250 g of yeast (1817, 28 g) for weight gain initial phase the control treatment (542.88 g), 250 g growth phase of yeast (1044.10) and the fattening was reported with 750 g of yeast ( 1232.02 g), feed conversion was variable for all phases which feature in the fattening stage was 500 and 750 g of yeast with 2.88. The greater body weight and dressing treatment was obtained 1000 g of yeast, the best cost / benefit ratio was recorded with 250 g of yeast with 0.09